Адаптивне координуюче керування співвідношеннями координат вершин взаємодіючих когнітивних карт у режимі імпульсних процесів - Romanenko, V. D.; Milyavsky, Y. L. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
The paper discusses a control problem of several complex systems described by cognitive maps. In particular, attention is paid to coordination between these systems, i.e. controlling the relations between vertices' coordinates of two complex systems. The stabilizing and coordinating control method for two interacting cognitive maps in impulse process under unknown or varying parameters of the maps was developed. The model of two interacting cognitive maps dynamics was derived. A stabilizing control algorithm for cognitive maps vertices coordinates was proposed. An optimality criterion which accounted for given vertices relations of two maps was introduced, and control method for keeping these relations during an impulse process was developed. Results were verified by two cognitive maps of cooperating banks. Significant stabilization time reduction of vertices coordinates and their relations was achieved.